It's like rocket science…only more complex: challenges and experiences related to managing pediatric obesity in Canada. Issue 3 (May 2014) - Avis, Jillian LS; Bridger, Tracey; Buchholz, Annick; Chanoine, Jean-Pierre; Hadjiyannakis, Stasia; Hamilton, Jill; Jetha, Mary M; Legault, Laurent; Morrison, Katherine M; Wareham, Anne; Ball, Geoff DC
<x xml:space="preserve">Abstract</x> Pediatric obesity is an urgent and complex public health issue. Approximately one-third of Canadian children are overweight or obese, a proportion that highlights the need for effective and accessible services to improve short- and long-term health risks. In our experience, we have encountered a number of challenges common in pediatric obesity management across our clinical and research centers. For the purpose of this review, these challenges and our real-world experiences are grouped as issues that span (i) caring for children, adolescents, and families, (ii) collaborating with colleagues and (iii) working within the health care system. Collectively, we highlight a number of lessons learned from our years of experience and detail ongoing initiatives designed to optimize health services for managing obesity for children and adolescents in Canada.